2021
DOI: 10.21203/rs.3.rs-146656/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on the Epidemiology of Knee and Shoulder Arthroscopy Procedures in a University Hospital Department in Poland

Abstract: Background: The purpose of our study was to comprehensively assess the effect of the COVID-19 pandemic on knee and shoulder arthroscopies performed in an orthopedic department of a university hospital in Poland.Methods: This study compared the data on shoulder and knee arthroscopy procedures performed in two different periods: the period of the COVID-19 pandemic in Poland (from March 4, 2020 to October 15, 2020) and the corresponding period prior to the pandemic (March 4, 2019–October 15, 2019). The study eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Therefore, 2019 was still the year of hospital promotion for arthroscopy service. The condition was similar to the results from a study by Kazubski et al in Poland which showed that the COVID-19 pandemic did not reduce the number of arthroscopies performed at their center and the mean age of the patients did not change [14].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, 2019 was still the year of hospital promotion for arthroscopy service. The condition was similar to the results from a study by Kazubski et al in Poland which showed that the COVID-19 pandemic did not reduce the number of arthroscopies performed at their center and the mean age of the patients did not change [14].…”
Section: Discussionsupporting
confidence: 89%